Cell Chromatography-Based Screening of the Active Components in Buyang Huanwu Decoction Promoting Axonal Regeneration. (29th September 2019) - Yan, Xiangli; Wang, Shengxin; Yu, Aiming; Shen, Xiao; Zheng, Haozhen; Wang, Lisheng
Abstract : Buyang Huanwu decoction (BHD), a popular formulation prescribed in traditional Chinese medicine (TCM) for the treatment of ischemic stroke, has been reported to have a potential role in promoting axonal regeneration. The purpose of the study was to screen and identify bioactive compounds from BHD using live PC12 cells coupled with high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS). Using this approach, we successfully identified six bioactive components from BHD. These components have protective effects on oxygen-glucose deprivation/reperfusion (OGD/R) injury to PC12 cells. Furthermore, calycosin-7-d -glucoside (CG) and formononetin-7-O- β -d -glucoside (FG) could upregulate the protein expression of growth-associated protein 43 (GAP-43) and brain-derived neurotrophic factor (BDNF). This study suggests that living cells combined with HPLC-MS/MS can be used for the screening of active ingredients in TCMs.